The ACE I allele is associated with increased risk for ruptured intracranial aneurysms. Issue 7 (1st July 2000) - Keramatipour, Mohammad; McConnell, Robert S; Kirkpatrick, Peter; Tebbs, Susan; Furlong, Robert A; Rubinsztein, David C
Abstract : Genetic and environmental factors play roles in the aetiology of ruptured intracranial aneurysms. Hypertension has been reported as a risk factor for intracranial aneurysm haemorrhage. We have tested if genotypes at the angiotensin converting enzyme ( ACE ) gene locus are associated with ruptured intracranial aneurysms. The insertion/deletion polymorphism in the ACE gene was genotyped in 258 subjects presenting in East Anglia with ruptured intracranial aneurysms (confirmed at surgery or angiographically) and 299 controls from the same region. ACE allele frequencies were significantly different in the cases and the controls (alleles χ 2 1 =4.67, p=0.03). The I allele was associated with aneurysm risk (odds ratio for I allele v D allele = 1.3 (95% CI=1.02-1-65); odds ratio for II v DD genotype = 1.67 (95% CI=1.04-2.66)). The I allele at the ACE locus is over-represented in subjects with ruptured intracranial aneurysms. These data are supported by non-significant trends in the same direction in two previous smaller studies. Thus, this allele may be associated with risk for ruptured intracranial aneurysms.